Pemberian Foot Message Terhadap Penurunan Intensitas Nyeri pada Ibu Post Operasi Sectio Caesarea di RSUD Ratu Aji Putri Botung - salma, siti; tina, agus; Veftisia, vistra (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2023)
Post partum Sectio caesarea (SC) is a way of giving birth to a fetus by making an incision in the uterine wall through the front wall of the abdomen. The obstacle that often occurs is the lack of knowledge of mothers about handling post SC pain intensity during post partum SC. The role of health workers is to help post partum SC mothers to understand how to handle post partum SC pain intensity with non-pharmacology. Treatment for pain intensity can be done by providing health knowledge to post partum SC mothers about foot massage and handling post partum SC pain intensity with complementary therapy in the form of foot massage. Mother's knowledge about nausea and vomiting and its handling is very important, in order to deal with the intensity of pain experienced during post partum SC. In connection with this problem, the community service program provides a solution to increase the knowledge of post partum SC mothers regarding handling pain intensity with foot massage. The activity began with a pre-test assessment related to post partum SC mothers and handling pain intensity with foot massage then health knowledge given to post partum SC mothers regarding pain intensity and its treatment with foot massage represented by 10 post partum SC mothers, next activity is evaluation by post-test. From these activities it was found that there was an increase in the knowledge of post partum SC mothers after being given health knowledge. Abstrak Post partum Sectio caesarea (SC) adalah suatu cara melahirkan janin dengan membuat sayatan pada dinding uterus melalui dinding depan perut. Kendala yang sering terjadi adalah kurangnya pengetahuan ibu mengenai penangan intensitas nyeri post SC pada masa post partum SC. Peran tenaga kesehatan untuk membantu ibu post partum SC agar mengerti cara penangan intensitas nyeri post partum SC dengan non farmakologi. Penangan dalam intensitas nyeri dapat dilakukan dengan memberikan pengetahuan  kesehatan pada ibu post partum SC tentang foot massage dan penanganan intensitas nyeri post partum SC dengan terapi komplementer berupa pijat foot massage. Pengetahuan ibu tentang mual muntah dan penangannya ini sangat lah penting, guna untuk menangani intensitas nyeri yang dialami selama post partum SC. Berkaitan dengan masalah tersebut, program pengabdian masyarakat memberikan solusi untuk meningkatkan pengetahun ibu post partum SC  mengenai penangan intensitas nyeri dengan pijat foot massage. Kegiatan diawali dengan penilaian pre- test yang berkaitan dengan ibu post partum SC dan penanganan intensitas nyeri dengan foot massage kemudian pengetahuan  kesehatan yang diberikan kepada ibu post partum SC mengenai intensitas nyeri serta penangannya dengan foot massage yang diwakili oleh 10 ibu post partum SC, kegiatan selanjutnya adalah evaluasi dengan post-test. Dari kegiatan tersebut didapatkan ada peningkatan pengetahuan ibu post partum SC setelah diberikan pengetahuan kesehatan.